Analysis of the protection of Indonesian migrant workers overseas in the perspective of government regulation No. 59 year 2021 - Rizky Maesarah Ibrahim (The International Journal of Politics and Sociology Research, 2023)
The opportunity to work abroad with a relatively high income compared to domestic income is an attraction for some citizens to go work abroad. The purpose of this study is to analyze the protection of Indonesian migrant workers abroad in the perspective of Government Regulation No. 59 of 2021. This type of research is normative juridical research. Data sources are primary and secondary data. In primary, data collection techniques are carried out by means of deep interviews at institutions or ministries as well as from international organizations and civil society organizations that have a commitment to the issue of placement of workers abroad. Secondary data collection through literature review (literature review). The results of the research show PP No. Policy.PMI protection is carried out in a mutually integrated manner between the Central Government, Representatives of the Republic of Indonesia, B2PMI, Regional Governments, and Village Governments in a coordinated manner. Until the village government was also involved in the migration process. The existence of this research is expected to be input for the government to coordinate with each other.